Is insufficient pulmonary air support the cause of dysphonia in chronic obstructive pulmonary disease?. Issue 4 (August 2018) - Hassan, Megahed M.; Hussein, Mona T.; Emam, Ahmed Mamdouh; Rashad, Usama M.; Rezk, Ibrahim; Awad, Al Hussein
Abstract: Objective: Optimal pulmonary air support is essential pre-requisite for efficient phonation. The objective is to correlate pulmonary and vocal functions in chronic obstructive pulmonary disease (COPD) to find out whether the reduced pulmonary function per se could induce dysphonia. Methods: In this prospective case-control study, sixty subjects with stable COPD underwent evaluation of pulmonary and vocal functions. The pulmonary functions measured include {Forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), FEV1/FVC ratio, peak expiratory flow (PEF), maximum mid-expiratory flow (MMEF)}. The vocal functions were {jitter, shimmer, noise-to-harmonic ratio, pitch perturbation quotient, amplitude perturbation quotient, maximum phonation time (MPT), sound pressure level, phonatory efficiency, resistance and power. A control group (n = 35) underwent the same measurements. These functions were compared between subjects and controls. Also, correlation of the vocal and pulmonary functions was conducted. Results: Thirty five (58.3%) of COPD subjects have dysphonia. The pulmonary functions were lower in all COPD group than in the control group ( P  < 0.001 for all parameters). Also, the FVC, FEV1, PEF and MMEF % of predicted values were significantly lower in subjects with dysphonia (n = 35) than those without dysphonia (n = 25) with P values 0.0018, <0.001, 0.0011 and 0.0026 respectively. In addition, the MPT in all subjects showed positive correlations to the 5 pulmonary functions ( P  = 0.004 for FEV1/FVC ratio and P < 0.001 for the rest). Also, the phonatory efficiency showed significant positive correlations with the pulmonary functions FVC, FEV1, PEF and MMEF ( P  = 0.001, 0.001, 0.002 and 0.001 respectively). Unlike efficiency, the phonatory resistance revealed significant negative correlations with these pulmonary functions in the same order ( P  = 0.001, 0.003, 0.002, 0.001 respectively). Conclusion: Dysphonia is a common comorbidity with COPD which attributed to multifactorial etiologies. The lower the pulmonary function in COPD patients is the more likely to have dysphonia. Decreased pulmonary function was associated with reduced MPT and phonatory efficiency but with increased phonatory resistance. The reduced pulmonary functions in COPD can be the underlying cause of the altered vocal function and dysphonia. Great part of this dysphonia is functional, and hence, can be corrected by voice therapy in compensated subjects. Further researches are needed to evaluate the efficacy of voice therapy in these patients.